ANALISIS PERBANDINGAN SISTEM PEMBERIAN KREDIT BANK KONVENSIONAL DENGAN PEMBIAYAAN BANK SYARIAH PADA USAHA MIKRO, KECIL, DAN MENENGAH - Chikmah, Achasih Nur (Jurnal Akuntansi AKUNESA, 2014)
This article explain of the difference between a system of credit provision byconventional banks, with financing by a bank syariah. Previous presentation ofresearch was expressed in a concise manner in order to provide an image ofabout the difference between conventional banks with a bank syariah. The resultshowed that the financing of syariah banks increased significantly. Through thisarticle is expected to given understanding more to the people either a debtor andcreditor for about conventional banks and syariah banks, and also expected to becapable of being consideration in election in store funds and borrow on bankinginstitution.Key words: bank conventional, bank syariah, financing